(untitled) (Bangladesh Journal of Botany, 2015)
Post harvest management of potato under sub-tropical conditions in Jammu division was studied. The losses due to poor handling and storage are reported to be in between 40 and 50%. The physiological and pathological causes observed before and during storage on potato crop revealed that 51.51% of respondents observed bruises on tubers followed by rooting (48.00%), chilling injury (44.89%), enlarged lenticels (42.67%) and sprouting up to 40.89%. DOI: http://dx.doi.org/10.3329/bjb.v43i3.21618 Bangladesh J. Bot. 43(3): 371-373, 2014 (December)